Totemism and human-animal relations in West Africa - Merz, Sharon, 1969- author.
1 online resource (208 pages).
Keywords: "This book explores human-animal relations amongst the Bebelibe of West Africa, with a focus on the establishment of totemic relationships with animals, what these relationships entail and the consequences of abusing them. Employing and developing the concepts of 'presencing' and 'the ontological penumbra' to shed light on the manner in which people make present and engage in the world around them, including the shadowy spaces that have to be negotiated in order to make sense of the world, the author shows how these concepts account for empathetic and intersubjective encounters with non-human animals. Grounded in rich ethnographic work, Totemism and Human-Animal Relations in West Africa offers a reappraisal of totemism and considers the implications of the ontological turn in understanding human-animal relations. As such, it will appeal to anthropologists, sociologists and anthrozoologists concerned with human-animal interaction"--